(untitled) (Research, Society and Development, 2020)
The Constitutional State gives the parties fundamental rights and guarantees of reserve and participation in the construction and control of judicial decisions, representing a true exercise of democracy. In this approach, it is vitally important to motivate and justify judicial decisions. The lack or deficiency in the grounds undermines the broad defense, as well as other constitutional procedural principles. In 2018, the Law No. 13.655 was published, which introduced changes in Law of Introduction to Brazilian Legislation (LINDB), with the aim of providing greater legal certainty, presenting some approaches that are related to the improvement of the basis of judicial decisions. The purpose of this work is to study the constitutional principle of a ample defense in the civil process, analyzing jointly the recent changes introduced in the Law on Introduction to Brazilian Law, especially in Articles 20 and 21, asking whether these changes contribute to achieve this principle. Using an exploratory and analytical method, through a bibliographical review, analysis of academic articles and standards, a careful reading was carried out, selecting the relevant aspects to finally proceed with a theoretical and analytical approach to the principle of ample defense introduced on the former law of Brazilian’ civil law procedures.